2021
DOI: 10.1186/s12991-021-00330-w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of gut microbiota and attention-deficit hyperactivity disorder (ADHD)

Abstract: Background Gut–brain axis (GBA) is a system widely studied nowadays, especially in the neuropsychiatry field. It is postulated to correlate with many psychiatric conditions, one of them being attention-deficit hyperactivity disorder (ADHD). ADHD is a disorder that affects many aspects of life, including but not limited to financial, psychosocial, and cultural aspects. Multiple studies have made a comparison of the gut microbiota between ADHD and healthy controls. Our aims were to review the exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 49 publications
0
35
0
1
Order By: Relevance
“…Although previous gut microbiome analyses on ADHD have mainly focused on pediatric samples [20,23,[26][27][28] and there is limited research on adults [22,24,], we focused our study on adulthood ADHD. Nevertheless, given that the gut microbiome evolves throughout the lifespan [16,52,53,], whether early-life exposure to environmental risk factors contributes to the gut microbiota and impacts neurodevelopment and mental health outcomes later in life remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous gut microbiome analyses on ADHD have mainly focused on pediatric samples [20,23,[26][27][28] and there is limited research on adults [22,24,], we focused our study on adulthood ADHD. Nevertheless, given that the gut microbiome evolves throughout the lifespan [16,52,53,], whether early-life exposure to environmental risk factors contributes to the gut microbiota and impacts neurodevelopment and mental health outcomes later in life remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, an increasing number of studies have shown gut microbiome alterations in neurodevelopmental disorders [14][15][16][17][18][19]. For ADHD, an increasing number of studies have reported that the gut microbial diversity, bacterial composition, and/or relative abundance of several bacterial taxa differ between patients and healthy controls [20][21][22][23][24][25][26][27][28]. Although not confirmed by others [20,22,27,], some studies found differences in microbiota alpha [23,28,] or beta diversity [23,24,] in ADHD.…”
Section: Introductionmentioning
confidence: 88%
“… 10 Many studies have shown that gut microbiota has a specific structure in neuropsychiatric diseases. Preliminary studies have explored the relationship between gut microbiota and psychiatric disorders such as depression, 11 autism, 12 Attention Deficit Hyperactivity Disorder (ADHD), 13 and eating disorders. 14 Gut microbiota is expected to be a new target for the treatment of psychosomatic diseases.The etiology and mechanism of various mental diseases are unknown, and the application of gut microbiota in mental diseases is still in its initial stage.…”
Section: Introductionmentioning
confidence: 99%
“…Caution should be used when comparing out results to those of previous studies. There is heterogeneity between previous studies regarding the sample size, study design, drug-naive status and technology applied for microbiome sequencing and cytokine analysis [ 3 , 75 ]. Further research is required to determine whether our findings can be extrapolated to other populations.…”
Section: Discussionmentioning
confidence: 99%